Microorganisms Related with Ventilator Associated Pneumonia (VAP) and their Antibiotic Sensitivity pattern - Wajahat Ahmed (Journal of Rawalpindi Medical College, 2014)
Background: To assess the microbiological growth and antibiotic sensitivity pattern in ventilator associated pneumonia (VAP). Methods: In this descriptive study nasobronchial lavages (NBL) were obtained by using a suction tube. These samples were processed using standard microbiological techniques. The frequency of the causative organisms was obtained by culturing the NBL samples on suitable media. The patients were analyzed by age, gender, the causative bacteria and their antibiotics susceptibility pattern. Results:A total of 48 cases of VAP were isolated. Monomicrobial infections were diagnosed in 32 patients and polymicrobial infections were diagnosed in 16 patients. Common causative agents were Acinetobacter baumanii, Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus and the least common were Proteus mirabilis, Klebsiella oxytoca, Acinetobacter johnsonii, Staphlococcus coagulase negative, Serratia odorifera, Serratia marcesens, Burkholderia cepacia, Citrobacter ferundii and Enterobacter cloacae. Conclusion:The etiological agents of VAP vary from common organisms to very resistant pathogens. With the increasing incidence of multi drug resistant organisms; its early isolation, detection, diagnosis and specific antibiotics are required to avoid hazardous outcomes.